1972
DOI: 10.1021/es60062a001
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of gaseous pollutants with solids. II. Infrared study of sorption of sulfur dioxide on magnesium oxide

Abstract: Sorption of S02 on MgO at 25 °C, and thermal decomposition at the sorbed layer in vacuum at temperatures up to 775 °C, were studied using infrared spectra recorded with a Fourier transform spectrometer. S02 was sorbed in at least four forms. The main interaction of S02 with degassed MgO resulted in the formation of monodentate-and bidentate-like surface sulfites which could only be removed by degassing at high temperatures. A reversible chemisorption occurred at high degrees of surface coverage. S02 was then p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
39
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 10 publications
5
39
0
Order By: Relevance
“…As mentioned in the Introduction, the absorption bands for δ ip (COH) of H 2 CO 3 , V as (COO -) of bidentate and bridged carbonates are very close to the band around 1273 cm -1 , and SO 4 2-may also contribute to the band at 1250 cm -1 . 21 Therefore, the assignment for the bands at 1578, 1333, and around 1273 cm -1 need be further carefully confirmed.…”
Section: Surface Species For the Heterogeneous Reaction Of Cos On Mgomentioning
confidence: 97%
See 1 more Smart Citation
“…As mentioned in the Introduction, the absorption bands for δ ip (COH) of H 2 CO 3 , V as (COO -) of bidentate and bridged carbonates are very close to the band around 1273 cm -1 , and SO 4 2-may also contribute to the band at 1250 cm -1 . 21 Therefore, the assignment for the bands at 1578, 1333, and around 1273 cm -1 need be further carefully confirmed.…”
Section: Surface Species For the Heterogeneous Reaction Of Cos On Mgomentioning
confidence: 97%
“…For example, the absorption bands for δ ip . 21 The bands at 1574 and 1327 cm -1 may also originate from surface carbonate 22 and physisorbed SO 2 , 23,24 respectively. Therefore, the assignment of infrared absorbance and molecular structure of HTC on mineral oxides need to be further carefully confirmed.…”
Section: Introductionmentioning
confidence: 98%
“…3. Peaks were counted if they were more than three times the noise at the peak position (Goldstein et al, 1981), and an approximate height was measured by overlaying a grid as shown in the figure. The known composition of the dust (Hanisch and Crowley, 2003) was used to determine relative sensitivity factors (RSF) for the different elements based on the EDX measurements on unreacted dust grains.…”
Section: Sem Analysismentioning
confidence: 99%
“…This study will only consider irreversible uptake, which can account for >98 % of uptake at low SO 2 concentrations (Adams et al, 2005;Goodman et al, 2001). The initial uptake coefficient on Sahara dust, γ = 4 × 10 −5 , is not dependent on RH, [SO 2 ] or O 3 (Crowley et al, 2010) which suggests SO 2 adsorption is the rate-limiting step, rather than subsequent reactions and oxidation (Ullerstam et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation